Quantisation‐based target detection for cooperative multiple input multiple output radar and communications with multiple stations - Zhen Wang; Qian He (IET Signal Processing)
Abstract Target detection is investigated for the emerging integrated radar and communication (IRC) systems. Consider the case, where multiple radar and communication stations are physically separated, possibly widely spaced, while working in a cooperative way. To utilise all available information for a final decision making, the radar stations that receive signals send their local measurements to a fusion centre (FC) through a wireless channel, say the backhaul network. For the purpose of decreasing communication traffic, the local measurements are quantised and then transferred to the FC. Three strategies for the quantisation and fusion are considered, where for the first method, local sensors quantise their test statistics, which are linearly fused at the FC (quantising test statistics and linear combination fusion), for the second method, the test statistics are quantised at the local sensors and optimally fused at the FC (quantising test statistics and optimal fusion), and for the third method, the received signals are quantizsd at the local sensors and optimally fused at the FC (quantising received signals and optimal fusion). The detection probability for each method is derived for the cooperative IRC system and compared with that of the non‐cooperative counterpart. It is proved that there is a detection performance gain through cooperation between the radar and communication systems and the cooperative IRC system can achieve the same performance as the non‐cooperative system with a fewer number of quantisation bits. The correctness of theoretical analysis is verified by simulations.